Research on the microstructural evolution mechanism and impact toughness of Ti-17 alloy with an initial basket-weave microstructure. (June 2022) - Yang, Ronggui; Zhao, Fei; Liu, Yuan; Shi, Kefei; Yin, Sheng; Fan, Mei
Abstract: In this work, the microstructural evolution mechanism and impact toughness of Ti-17 alloy with an initial basket-weave microstructure were systematically studied. Ti-17 alloys were rolled by 0, 20%, 40% and 60% at 860 °C, and afterward immediately aged at 600 °C for 8 h. The main evolved microstructural features were the globularization of the lamellar primary α phase (αp ) and the precipitation of the lamellar secondary α phase (αs ). The globularization fraction of αp raised, while the fraction of precipitated αs first increased and then decreased as the thickness reduction increased from 0% to 60%. The globularization behavior of αp originated from the combination of the αp recrystallization and the cutting of the β phase. The αs precipitation was affected by dislocation density in the β phase. In the thickness reduction range of 0–40%, the microstructural evolution of the α phase (αp and αs ) enhanced impact toughness, which was largely attributed to the higher amount of precipitated αs . However, at the thickness reduction of 60%, the impact toughness sharply decreased due to the high globularization fraction of αp and the minor precipitation of αs negatively affected the crack propagation inhibition. Graphical Abstract: To reveal the microstructure evolution mechanism of α phase and the influence of microstructural variation on impact toughness of Ti-17 alloy, the globularization mechanism, precipitation mechanism of α phase, and TEM microstructures near the crack initiation zone were investigated in detail. ga1